Green synthesis of size-controlled silver nan particles and their anti-cancer potentiality - Kabir, M. F.; Rahman, M. Z.; Ferdousy, J.; Atique Ullah, A. K. M; Foysal, M.; Razzakul, I. M.; Rahman, M. M. (Malaysian NANO-An International Journal, 2023)
Silver nanoparticles (Ag-NPs) are now well recognized as one of the most prevalent kinds of materials that are put to use in a wide variety of biomedical applications, most notably as an anti-cancer agent. In the current investigation, Ag-NPs were effectively produced by reducing silver ions by employing the leaf extract of Artocarpus heterophyllus as a source of reducing and capping agents. By altering the quantity of the silver nitrate solution, we successfully synthesized three distinct kinds of Ag-nanoparticles that were mediated by Artocarpus heterophyllus leaf extract. The X-ray diffraction (XRD) analysis first confirmed the formation of metallic silver, where peaks were found at fixed angles. XRD method was also used to validate the crystal geometry of the Ag-NPs, revealing that the Ag-NPs had a face-cantered cubic structure. The calculated average crystallite sizes of Sample-1 Ag-NPs, Sample-2 Ag-NPs, and Sample-3 Ag-NPs were 20.34 nm, 16.99 nm, and 18.88 nm, respectively. Ag-NPs were also confirmed from EDX analysis and firm Ag peaks, including several organic compound peaks. The nanoparticle’s range was between 120 nm and 220 nm, and the average particle size was near 170 nm, as found in the SEM image, and accumulation was observed in the SEM image. Using Fourier Transform Infrared (FT-IR) spectroscopy, we determined the functional groups of organic compounds that might be responsible for reducing agents and the presence of capping agents on the surface of Ag-NPs. The cell viability test was used to assess the cytotoxicity using the HeLa cell, a human carcinoma cell. The results revealed that the produced Ag-NPs demonstrated toxicity against carcinoma cells.